1997
DOI: 10.1073/pnas.94.26.14506
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy correlated 100% with chemical transformation of Chinese hamster cells

Abstract: Aneuploidy or chromosome imbalance is the most massive genetic abnormality of cancer cells. It used to be considered the cause of cancer when it was discovered more than 100 years ago. Since the discovery of the gene, the aneuploidy hypothesis has lost ground to the hypothesis that mutation of cellular genes causes cancer. According to this hypothesis, cancers are diploid and aneuploidy is secondary or nonessential. Here we reexamine the aneuploidy hypothesis in view of the fact that nearly all solid cancers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 89 publications
4
111
0
Order By: Relevance
“…Fifth, this finding implies that a substantial portion of the phenotypic uniqueness (and by extension, the heterogeneity in clinical behavior) among patients' tumors may be traceable to underlying variation in DNA copy number. Sixth, this finding supports a possible role for widespread DNA copy number alteration in tumorigenesis (17,18), beyond the amplification of specific oncogenes and deletion of specific tumor suppressor genes. Widespread DNA copy number alteration, and the concomitant widespread imbalance in gene expression, might disrupt critical stochiometric relationships in cell metabolism and physiology (e.g., proteosome, mitotic spindle), possibly promoting further chromosomal instability and directly contributing to tumor development or progression.…”
Section: Discussionmentioning
confidence: 61%
“…Fifth, this finding implies that a substantial portion of the phenotypic uniqueness (and by extension, the heterogeneity in clinical behavior) among patients' tumors may be traceable to underlying variation in DNA copy number. Sixth, this finding supports a possible role for widespread DNA copy number alteration in tumorigenesis (17,18), beyond the amplification of specific oncogenes and deletion of specific tumor suppressor genes. Widespread DNA copy number alteration, and the concomitant widespread imbalance in gene expression, might disrupt critical stochiometric relationships in cell metabolism and physiology (e.g., proteosome, mitotic spindle), possibly promoting further chromosomal instability and directly contributing to tumor development or progression.…”
Section: Discussionmentioning
confidence: 61%
“…Given that inactivation of p53 in tetraploid cells results in progression toward aneuploidy, it is evident that tetraploid arrest may be an important means by which p53 preserves genomic integrity. Because aneuploidization is tightly correlated with tumor formation (Rabinovitch et al, 1989, Li et al, 1997Duesberg et al, 1998;Lengauer et al, 1998), we conclude that the tetraploidy checkpoint function of p53 may be essential to its role as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Most human solid tumors are genetically unstable, and the loss or gain of complete chromosomes is the predominant form of genetic instability . Aneuploidy is an important element of tumorigenesis (Li et al, 1997), and inactivation of p53 is probably an important element of this process (Harvey et al, 1993). Because we show here that the inactivation of p53 in tetraploid cells results in aneuploidization following the completion of a single tetraploid cell cycle, and because the tetraploid state is a frequent precursor to aneuploidization in solid human tumors (Shackney et al, 1989), we propose that the prevention of aneuploidy by blocking the rereplication of tetraploid cells that result from failures in mitosis may be a vital function of p53.…”
Section: Role Of Tetraploidy Checkpoint In Maintenance Of Genomic Intmentioning
confidence: 99%
“…Li et al 53 concluded that aneuploidy was the cause rather than a consequence of transformation, based on chromosome analysis of transformed cells. Duesberg et al 54 also showed that aneuploidy resulted in karyotypic and phenotypic heterogeneity of cancer cells.…”
Section: Discussionmentioning
confidence: 99%